Developing a numerical hydrogeologic model of the Verlorenvlei Catchment to evaluate the groundwater budget - Germeshuisen, Ezelna (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.